PENGARUH IDENTITAS ETIS ISLAM DAN MARKET SHARE TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN INDONESIA TAHUN 2014-2017 - Mokhammmad Khukaim Barkhowa; Hardi Utomo (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This study aims to find out and explain: the influence of Islamic ethical identity and market share on sharia banking financial performance registered with the Indonesian financial services authority in 2014-2017. The population in this study is a sharia public bank registered in the Financial Services Authority 2014-2017. The sample of this study was 11 sharia public banks sent at the Financial Services Authority 2014-2017 which were taken using purposive sampling. Analysis of the data used is multiple linear regression analysis. The results of hypothesis testing that prove ethical ethical identity are not significantly related to financial performance seen from the return of assets so that these results are not in accordance with the hypothesis proposed in this research. The results of hypothesis testing show a positive and significant statistical market share of financial performance seen from the return of assets so that these results are in accordance with the hypothesis proposed in this research.